2015
DOI: 10.2147/idr.s88725
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-based nationwide surveillance of antimicrobial resistance in Ghana

Abstract: Global efforts are underway to combat antimicrobial resistance (AMR). A key target in this intervention is surveillance for local and national action. Data on AMR in Ghana are limited, and monitoring of AMR is nonexistent. We sought to generate baseline data on AMR, and to assess the readiness of Ghana in laboratory-based surveillance. Biomedical scientists in laboratories across Ghana with capacity to perform bacteriological culture were selected and trained. In-house standard operating protocols were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
79
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 30 publications
13
79
0
2
Order By: Relevance
“…Extremely high percentage resistance to ampicillin and tetracycline was observed, which concurs with previous studies on enteric organisms in Ghana [ 30 , 31 ]. In enteric organisms, tetracycline resistance is mediated by tet (A) and tet (B) genes that encode efflux proteins.…”
Section: Discussionsupporting
confidence: 91%
“…Extremely high percentage resistance to ampicillin and tetracycline was observed, which concurs with previous studies on enteric organisms in Ghana [ 30 , 31 ]. In enteric organisms, tetracycline resistance is mediated by tet (A) and tet (B) genes that encode efflux proteins.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, a comparison of DALYs across eleven countries worldwide revealed that Ghana's total DALYs for the aforementioned infections was significantly higher than the mean [23]. Furthermore, increasing trends in AMR rates in Ghana, evidenced by clinical studies, further reflect this concern [2,24]. An estimated 41% of outpatients in Ghana receive at least one antibiotic [2].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Ghana have reported K. pneumoniae as a major pathogen responsible for UTI (Gyasi-Sarpong et al, 2014). A laboratory-based nationwide surveillance of antimicrobial resistance in Ghana by Opintan and co-workers reported that K. pneumoniae represented 1.06% of all bacterial infections and 1.4% of Gram-negative bacilli (Opintan et al, 2015). Agyepong et al (2018) indicated an increased K. pneumoniae resistance of 19% (37/200) of Gram-negative bacteria in their study on MDR bacterial infections in a teaching hospital in Ghana.…”
Section: Introductionmentioning
confidence: 99%